Single motherhood in East and West Germany: What can explain the differences? - Uwe Jirjahn; Cornelia Struewing (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2015)
The share of single mothers is higher in East Germany than in West Germany. Using data from the Socio-Economic Panel (SOEP), we examine two transmission channels leading to single motherhood, namely out-of-partnership births and separations of couples with minor children. Women in East Germany have both a higher probability of out-of-partnership birth and a higher probability of separation. We find no evidence that availability of child care plays a role in the differences between East and West Germany. The differences in single motherhood appear to be rather driven by cultural and economic factors.
Keywords: J12; J13; P20; 330; out-of-partnership birth; separation of couples; cohabitation; child care; unemployment; culture